Exploring the Impact of Entrepreneurial Knowledge and Creativity on Entrepreneurial Behavior: The Mediating Role of Self-Efficacy - Prabandari, Sri Palupi; Yulianti, ida; Ismail, Taufiq; Irma Kurniasari (Jurnal Mebis, 2024)
Entrepreneurship contributes significantly to economic growth by creating opportunities and reducing unemployment and improving community welfare. This study examines the role of entrepreneurial knowledge and creativity in shaping entrepreneurial behavior with self-efficacy as a mediating variable. The data of this study were obtained by distributing questionnaires to young entrepreneurs in Malang City. The data obtained were then analyzed using PLS. The results showed that entrepreneurial knowledge and creativity have a positive effect on self-efficacy, which then mediates entrepreneurial behavior. This study provides implications for the design of targeted Education Policy to encourage the development of human capital, innovation and economic growth.